HUBUNGAN FENOMENA PROBLEMATIKA POLA TIDUR DENGAN KUALITAS PEMBELAJARAN DI MA MADRASATUL QUR`AN TEBUIRENG JOMBANG: Jurnal Ilmu Pendidikan - Syafi'ut Thoriq, Naf'an Rizal; Andreastya, Vian Hanes (Al Tadib : Jurnal Ilmu Pendidikan, 2020)
This article is entitled the relathionship between the phenomenon of sleeping patterns and the quality of learning in MA Madrasatul Qur'an Tebuireng Jombang. The purpose of this research is: 1) To describe the phenomenon of sleeping patterns and the quality of learning in MA Madrasatul Qur'an Tebuireng Jombang. 2) To describe the quality of learning in MA Madrasatul Qur'an tebuireng Jombang. 3) To describe the relathionship between the phenomenon of sleeping patterns and the quality of learning in MA Madrasatul Qur'an Tebuireng Jombang. Researcher used a quantitative approach to design expost facto. While the data analysis technique is using the Spearman Correlation Statistics. The results show that: 1) The percentage of sleeping patterns for MA Madrasatul Qur'an Jombang students is 64%. 2) While the percentage of the quality of learning in MA Madrasatul Qur'an Tebuireng Jombang is 71%. 3) Based on the results of hypothesis testing using the Spearman Statistical Correlation technique produces sig. values. i.e.0,003. It means that there is a relathionship between sleeping pattern problems with the quality of learning. While the correlation Coofficient number is 0,291. This means that correlation number shows a positive (comparable) value.